2014
DOI: 10.1007/s11596-014-1284-2
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of LncRNAH19 and MiR-675 promotes migration and invasion of human hepatocellular carcinoma cells through AKT/GSK-3β/Cdc25A signaling pathway

Abstract: LncRNAH19 has been implicated as having both oncogenic and tumor suppression properties in cancer. LncRNAH19 transcripts also serve as a precursor for miR-675. However, it is unknown whether LncRNAH19 and miR-675 are involved in the migration and invasion of hepatocellular carcinoma (HCC) cells. The purpose of this study was to investigate the effect and mechanism of LncRNAH19 and miR-675 on migration and invasion of HCC cells. The migration and invasion of HCC cells were measured by Transwell migration and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…Also, results of experiments on cells verified that the increased expression of HOST2 increased cell proliferation, as well as cell migration and invasion, which was consistent with previous study that the increased expression of LncRNA in HCC tissues was mainly related to the invasion of HBV [19]. Multiple LncRNAs are demonstrated to be correlated to HCC, Wang et al [20] indicated that LncRNA-UCA1 up-regulation promotes HCC progression accompanied by miR-216b inhibition, and Lv et al showed that LncRNA H19 and miR-675 inhibition contributes to migration and invasion of HCC [21]. HOST2 is a novel gene that contains plentiful copies of retroviral-related sequences [14].…”
Section: Discussionsupporting
confidence: 85%
“…Also, results of experiments on cells verified that the increased expression of HOST2 increased cell proliferation, as well as cell migration and invasion, which was consistent with previous study that the increased expression of LncRNA in HCC tissues was mainly related to the invasion of HBV [19]. Multiple LncRNAs are demonstrated to be correlated to HCC, Wang et al [20] indicated that LncRNA-UCA1 up-regulation promotes HCC progression accompanied by miR-216b inhibition, and Lv et al showed that LncRNA H19 and miR-675 inhibition contributes to migration and invasion of HCC [21]. HOST2 is a novel gene that contains plentiful copies of retroviral-related sequences [14].…”
Section: Discussionsupporting
confidence: 85%
“…It has also been demonstrated that multiple LncRNAs are associated with HCC. For example, Wang et al revealed that LncRNA-UCA1 upregulation and miR-216b inhibition could promote the progression of HCC [36], and Lv et al showed that increased LncRNA H19 contributes to migration and invasiveness of HCC cells, which is accompanied by miR-675 downregulation [37]. STAT3 signaling promotes HCC progression through the suppression of apoptosis through the induction of [38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their analysis also indicated that by altering the epigenetic activation of miR-200 with cooperation of the protein complex hnRNP U/PCAF/RNA Pol II, H19 could suppress HCC metastasis and cause EMT. Similarly, based on the conclusion of Jun et al [78], H19, working together with miR-675, promotes migration and invasion of HCC through the AKT/GSK-3β/Cdc25A signaling pathway, providing evidence that this type of lncRNA could be a potent diagnostic biomarker and therapeutic target for HCC.…”
Section: H19mentioning
confidence: 93%